EFFECTIVENESS OF APPLYING DEMONSTRATION METHODS BASED ON MIND MAPPING IN UNDERSTANDING WUDU MATERIALS AT SMA NEGERI 9 BULUKUMBA (International Conference on Social and Islamic Studies, 2022)
This thesis discusses the "Effectiveness of Applying Demonstration Methods based on Mind Mapping in Understanding Wudu Materials at SMA Negeri 9 Bulukumba" which aims to; 1) Describe students' understanding of ablution material taught without using the Mind Mapping-based demonstration method at SMA Negeri 9 Bulukumba Regency; 2) Describe the understanding of students' ablution material taught by applying the Mind Mapping-based demonstration method at SMA Negeri 9 Bulukumba Regency; 3) Describe whether there is effectiveness in applying the Mind Mapping-based demonstration method in understanding ablution material at SMA Negeri 9 Bulukumba Regency. This research is a quantitative research and uses experimental methods. The instrument used in this research is test. Then, the data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that; 1) The description of the understanding of ablution material for class XI MIPA 2 students, who were taught without using the Mind Mapping-based demonstration method, was included in the "very low" category. 2) A description of the understanding of ablution material for class XI MIPA 2 students, who are taught using the Mind Mapping-based demonstration method, is included in the "high" category. 3) Based on the significance test, it can be concluded that tcount = 30.86 > from t table, namely 2.16. So, Ho is rejected and Ha is accepted, meaning that the application of the Mind Mapping-based demonstration method is effective in understanding ablution material at SMA Negeri 9 Bulukumba. Suggestions in this study are; 1) Teachers as implementers of education should have the ability to choose suitable learning methods in providing learning; 2) All things that hinder the learning process must be repaired, and learning objectives must be carefully arranged; 3) It is suggested to each student to further increase motivation in learning and be even more active.